Impact of vaccination on the incidence of varicella hospitalizations in a state in Southeast Brazil - Aline Ciabotti Dias; Leiner Resende Rodrigues; Altacílio Aparecido Nunes; Sybelle de Souza Castro (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: This study aimed to analyze cases of complicated varicella and the impact of varicella vaccination in Minas Gerais, Brazil. METHODS: This was a time series study of a territorial basis using data on varicella cases from 2010 to 2016, which was provided by the State Health Department of Minas Gerais on . Descriptive statistics were used for the analysis, and the generalized linear regression model proposed by Prais-Winsten was used for the time tendency, adopting a significance level of 5% and the integrated autoregressive modeling of moving averages. RESULTS: There were 1,635 cases of varicella; out of which cellulitis (44%) was the predominant complication. The home-acquired cases were 38.9% and 464 cases (40.6%) were not previously vaccinated. There was a significant decrease in the incidence coefficient when comparing the pre- and post- immunization periods, from 1.95 cases/100,000 inhabitants in 2010 to 0.24 cases/100.000 inhabitants in 2016 (p<0.05). There was a higher incidence of cases recorded among males, with higher prevalence in the age group of 1-4 years (54.7%). Lethality was higher between 5-9 years of age (44%). Mortality was higher in the age group of 0-4 years and among females (2.58/100,000 inhabitants/year). The overall trend of the incidence coefficient was a decreasing one, with an annual percentage variation. CONCLUSIONS: The number of complicated varicella cases notified decreased, coincidentally, in the post-immunization period. However, the immunization coverage period was restricted for the assessment of the correlation between immunization coverage and incidence.